Exploring Students-Teacher Interaction in Dialogic Reading of Descriptive Texts - Annisa Sita Herdanti; Hilmansyah Saefullah (Edumaspul: Jurnal Pendidikan, 2021)
The interaction between students and teachers in the classroom is an important part of language learning. Dialogic reading is one of the learning strategies that can be appropriate to facilitate EFL students’ and teacher’s interaction in the classroom. The dialogic reading emphasizes the interaction between adults and children in this case students and teacher, the teacher used a variety of question techniques such as ‘PEER’ and ‘CROWD’ strategy of dialogic reading. Therefore, this research aims to explore the students and teacher interaction on dialogic reading in learning reading English text. The researcher chooses micro-ethnography method to get a clear description of the interaction between the teacher and students in an EFL setting. It applied in Junior High School in Purwakarta, with three students as a participants. The result of this research showed that the teacher interacted with students’ by kind of interaction, and the students interacted with the teacher by kind of interaction too, and also the students a quiet active when they were asked by the teacher. In the classroom between teacher and students should have the willingness to participate in the interaction.